(untitled) (Research, Society and Development, 2020)
The aim of this study is to analyze the factors that stimulate generational succession, from the perspective of farmers in the municipality of Condor-RS. The sample is non-probabilistic and for convenience. 64 questionnaires were applied to farmers in the municipality of Condor-RS, from July to August 2019. The data were analyzed using Exploratory Factor Analysis, Cluster Analysis and Descriptive Statistics. Using statistical techniques, two groups of farmers were identified. The first is formed by farmers who are less sensitive to factors that influence succession processes (19 farmers). The second group is made up of farmers more sensitive to factors that influence succession (45 farmers). In general, the farmers who contributed to this research are mostly male, over the age of 50 and with low schooling. With regard to the continuity of properties, among the total respondents, farmers without succession predominate, 78.12% (51 farmers). In terms of stratified analysis, considering the set of variables, both for characterization of farmers and properties, it is important to consider that there are differences between the groups analyzed. It was found that farmers less sensitive to the factors that motivate succession are those where the lack of successors predominates, the longest activity on the property, the older age of the head of the family and the size of the properties is smaller. Together, these aspects may be, to a greater or lesser degree, hindering the possibilities of succession in the analyzed rural environment.